Can we afford to communicaten ; Utilizing the best of communication devices [soundrecording] / Warncke, Ruth. - Warncke, Ruth.; Whitenack, Carolyn I.; Warncke, Ruth.; Whitenack, Carolyn I. (Los Angeles CREDR Corp., 1973)
The sources and costs of various kinds of non-print media are given. A library is seen as a series of functions which sweeps beyond its walls touching all aspects of the community. Describes and documents how and where this is being done and with what effect.
Can we afford to communicaten / Carolyn I. Whitenack (35 min) -- Utilizing the best of communication devices / Ruth Warncke (35 min)
American Library Association, 91st annual conference. Media: man, material, machine.
Keywords: Libraries -- Nonbook materials -- Congresses; Nonbook materials -- Congresses